Uyku kalitesi ile yeme bozuklukları arasındaki ilişkide sorunlu telefon kullanımı ve dürtüselliğin aracı rolü - Gündoğdu, Ümmügülsüm (Journal of Dependence, 2022)
Objective: Both sleeping and eating habits have a major influence on the development of psychopathology and its course in adolescents. Studies have examined the relationships between sleep quality, impulsivity that is defined as acting without thinking and eating disorders (ED). The importance of using mobile phones in our daily lives is a well-known fact. However, in recent years, psychiatric disorders related to problematic mobile phone use (PMPU) have also attracted attention. The present study examined impulsivity and PMPU as two factors that can mediate the relationship between ED and sleep quality. Method: The sample comprised 108 adolescents aged between 12 to 18 years. They completed self-report questionnaires that assessed their impulsivity, sleep quality, symptoms and severity of ED, and PMPU. Results: Binge-eating and impulsivity were significantly higher in adolescents with sleep disorders. The PMPU scores were similar in adolescents with and without sleep disorders. The PMPU scores, motor and non-planning scales of impulsivity, and total scores of impulsivity, were similar in both adolescents with and without eating problems. Linear regression analysis revealed that binge eating was significantly positively correlated with sleep quality and the total impulsivity scores. Conclusion: Thus, sleep disturbance and impulsivity were associated with binge-eating disorder directly. Sleep disturbance mediated only bingeeating behavior through impulsivity. The PMPU did not mediate any association between sleep disturbances and eating disorders.